Karakteristik Fisis Tanah dengan Penambahan Serbuk Eceng Gondok - Ardhiya Rachmala Zedi; Athaya Zhafirah; Rudy Febrijanto (Jurnal Konstruksi, 2026)
The population of water hyacinth in Situ Bagendit has grown rapidly, causing ecological impacts, including the coverage of the water surface that leads to a decline in aquatic ecosystem quality. On the other hand, dried water hyacinth contains compounds such as cellulose, lignin, and silica, which have potential for use as soil stabilization material. This study aims to evaluate the effect of adding water hyacinth powder on the physical properties of clay soil with mixture variations of 0%, 3%, 6%, and 9% by weight of the original soil. The experimental method includes water content testing, sieve analysis, liquid limit, plastic limit, shrinkage limit, specific gravity, bulk density, and compaction tests, all conducted at the Laboratory of the Garut Institute of Technology. The results show that the addition of water hyacinth powder causes significant changes in the physical properties of clay soil, with the most optimal effect occurring at the 9% mixture. Practically, these findings indicate that water hyacinth powder has the potential to be used as an environmentally friendly additive to improve subgrade soil characteristics, particularly for light construction applications and foundation improvement.